Baby boomers and hearing loss : a guide to prevention and care - Burkey, John M., 1959- (Rutgers University Press, 2006)
Baby boomers have always had high expectations. As a generation, they have worked hard and played hard. They have been distinguished for their trendsetting and active lifestyles. As they move into their senior years, this ambitious constituency of 76 million Americans continues to demand a lot from life, and to offer much as well. Compared with every generation that preceded them, baby boomers are anticipated to continue professional careers later into their retirement years, engage in more vigorous activities, and live significantly longer. Their lifestyles make learning to prevent and treat hearing loss - a disability that used to be considered an unfortunate but inevitable aspect of aging - more important than ever. In "Baby Boomers and Hearing Loss", audiologist John M. Burkey shows readers how they can continue to enjoy youthful living, regardless of whether their hearing abilities are undiminished or severely compromised. In a reassuring and straightforward style, Burkey explains the typical causes of hearing loss, from genetic factors to years of exposure to loud noises, and demystifies the sometimes confusing results of a hearing test.; Fortunately, new technologies and advances in medicine have made it easier to detect signs of initial hearing loss and to prevent it from becoming a serious problem. For those who have already sustained some damage, the author suggests ways to manage daily activities by using a range of techniques, equipment, and medical procedures. His suggestions include minor changes, such as using a vibrating alarm clock rather than one that is sound-based. More dramatic but often highly effective options, including reconstructive surgery, cochlear implants, and bone-anchored hearing aids, are also described. In his previous award-winning book, "Overcoming Hearing Aid Fears: The Road to Better Hearing", Burkey addressed common fears, concerns, and misconceptions that people have about choosing and using hearing aids. In this second indispensable volume, he offers a comprehensive guide on how to cope with and prevent hearing impairment. For a generation that refuses to slow down or quietly accept limitations, this book is essential reading.